2021
DOI: 10.3390/ijms22126258
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Microenvironment Modulates the Transfer of Mutated TP53 Mediated by Tumor Exosomes

Abstract: Exosomes released from tumor cells are instrumental in shaping the local tumor microenvironment to allow cancer progression. Recently, it has been shown that tumor exosomes carry large fragments of dsDNA, which may reflect the mutational status of parental cells. Although it has been described that a stressful microenvironment can influence exosomal cargo, the effects on DNA packing and its transfer into recipient cells have yet to be investigated. Here, we report that exosomes derived from SW480 (human colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The author also proved that LPS activated TLR4 of colon cancer cell SW480 and promoted the packaging of mutant TP53 in exosomes but could not promote the selective packaging of the KRAS gene. It indicates that the mechanism of gDNA packaging to exosomes is not random ( Domenis et al, 2021 ). More and more experiments proved that exosomes derived from primary tumors could be loaded with specific molecules ( Stobiecka et al, 2019 ; Baris et al, 2021 ), and the expression or lack of these molecules is helpful to the phenotype transformation of recipient cells.…”
Section: Colorectal Cancer Microenvironment Plays An Essential Role O...mentioning
confidence: 99%
“…The author also proved that LPS activated TLR4 of colon cancer cell SW480 and promoted the packaging of mutant TP53 in exosomes but could not promote the selective packaging of the KRAS gene. It indicates that the mechanism of gDNA packaging to exosomes is not random ( Domenis et al, 2021 ). More and more experiments proved that exosomes derived from primary tumors could be loaded with specific molecules ( Stobiecka et al, 2019 ; Baris et al, 2021 ), and the expression or lack of these molecules is helpful to the phenotype transformation of recipient cells.…”
Section: Colorectal Cancer Microenvironment Plays An Essential Role O...mentioning
confidence: 99%
“…For example, Domenis et al reported that exosomes derived from SW480 (human colorectal adenocarcinoma cell line) cells contributed to transferring dsDNA fragments containing the entire coding sequence of both tumor protein p53 ( TP53 ) and KRAS proto-oncogene ( KRAS ) genes, harboring the TP53 c.818G > A and KRAS c.35G > T typical mutations. In addition, the stimulation of lipopolysaccharides (LPS) could promote the packaging of the TP53 gene rather than KRAS gene indicating the selective package of gDNA 26 . Furthermore, recent studies have also suggested the essential role of exosomal DNA in the development of drug resistance in malignant cells.…”
Section: Exosomal Cargoes Mediating Tumor Drug Resistancementioning
confidence: 99%
“…However, it is particularly important that this system can adapt quickly to stress (e.g., genotoxic oncotherapies) by increasing micronucleus formation and the concomitant packaging of gDNA into sEVs (sEV-gDNA) ( Figure 1D ) ( 24 ). The dynamic adaptation of sEV-mediated DNA release is further supported by the changing quality and/or quantity of transported genetic content (e.g., the proportion of genomic and mitochondrial (mt) DNA, as well as the average size of DNA fragments) upon diverse environmental effects ( 29 , 30 ).…”
Section: Release Of Dna Through Sev Secretionmentioning
confidence: 99%
“…It may lead to an increased gDNA content in MVB-originated sEVs (i.e., exosomes) ( 24 , 27 ). The rapid change in gDNA content of exosomes by existing stress factors (e.g., effects of artificial selection or the pro-inflammatory microenvironment) have been observed ( 24 , 29 , 30 ), however, it is not known how similar stress conditions may regulate the non-MVB-originated sEV release. Presumably, these sEV release pathways may change dynamically upon exposure to various microenvironmental or therapy-induced stress factors.…”
Section: Release Of Dna Through Sev Secretionmentioning
confidence: 99%
See 1 more Smart Citation